Modified waterproof coiled material asphalt and preparation method thereof
Modifying nanosilica through low-temperature plasma treatment and cycloalkane acid grafting technology, the cracking problem of modified waterproof roll asphalt under high and low temperature conditions and the poor compatibility of nanomaterials are solved, achieving higher viscosity Adhesion and durability.
Patent Information
- Application Number
- CN202311018997.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
The existing modified waterproof coil asphalt is prone to cracking under high and low temperature conditions, and the compatibility of nanomaterials and asphalt is poor, resulting in a decrease in adhesion and affecting durability.
The nanosilica is surface-treated by low-temperature plasma and chromatocyclic acid in the cycloalkane acid dispersion to improve the compatibility and dispersion of the nanosilica and matrix asphalt.
It significantly improves the high-temperature and low-temperature properties of the modified waterproof coil asphalt, enhances adhesion and durability, prevents the peeling of nano-silica, and extends the service life of the waterproof coil.
Abstract
Description
Technical Field
[0001] The invention discloses a modified waterproofing roll asphalt and a preparation method thereof, belonging to the technical field of waterproofing roll asphalt. Background Art
[0002] Modified waterproofing membranes are widely used in the field of building waterproofing due to their superior performance. Since waterproofing membranes are organic waterproofing materials, while building materials are inorganic materials, the adhesion between waterproofing membranes and building materials is poor, and it is easy for the waterproofing membranes and building materials to peel off during use. At the same time, as the use time of waterproofing membranes increases, the waterproofing membranes shrink and expand with the change of temperature, which makes the waterproofing membranes prone to cracking, affecting the durable performance of the waterproofing membranes.
[0003] In the prior art, nanomaterials are added to asphalt in waterproofing rolls to improve the high temperature and mechanical properties of waterproofing rolls. However, nanomaterials are inorganic oleophobic materials and have poor compatibility with oily materials such as asphalt. If they are not treated, the adhesion between the nanomaterials and asphalt will deteriorate, causing the nanomaterials to peel off from the waterproofing rolls, affecting the low temperature performance of the waterproofing rolls. At the same time, after the nanomaterials peel off, the high temperature performance of the waterproofing rolls will decrease, causing the deformation of the waterproofing rolls with the temperature to increase, causing the rolls to crack, affecting the performance of the rolls.
[0004] Patent CN103013182A discloses a method for surface modification of nano-silica, which uses KH-550 to ultrasonically modify the surface of silica nanoparticles, thereby improving the dispersibility and anti-aging properties of the silica nanoparticles. However, this method has limited surface modification capabilities for nano-silica in actual applications and has limited effects on improving dispersibility.
[0005] Patent CN108274844B discloses the use of SBS modifiers and polyamide wax to improve the dispersibility of nano-silica and nano-zeolite in asphalt, but the nano-silica itself does not actually change its surface, and the slow separation of asphalt as inorganic and organic components during long-term use is still not effectively improved. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a modified waterproof roll asphalt having high durability and compatibility with inorganic materials and a preparation method thereof.
[0007] The technical solution adopted by the present invention to solve the technical problem is: a modified waterproof roll asphalt, characterized in that the raw materials include 30-45 parts of base asphalt, 5-15 parts of petroleum resin, 12-22 parts of SBS polymer, 12-24 parts of solubilizer, and 15-25 parts of modified nano silicon dioxide in parts by weight; Wherein, the modified nano silicon dioxide is modified by the following steps: 1) Low temperature plasma surface treatment of nano-silicon dioxide; 2) After the nano-silica and cyclohexane acid dispersion are mixed and stirred evenly, react at 70-80°C for 100-200 minutes; 3) Separating, washing and drying the products to obtain modified nano-silica.
[0008] In low-temperature plasma discharge treatment, low temperature refers to the temperature generated under the discharge conditions. After low-temperature plasma discharge treatment, the surface of the nano-silica is activated, a large number of activation reaction points are generated, and the hydroxyl active groups on the surface of the nano-silica are increased, which is conducive to the subsequent complete grafting reaction. The grafting of cyclopentane acid onto the nano-silica can increase the compatibility of the nano-silica with the matrix asphalt. By using high-speed shear dispersion, the nano-silica treated with plasma is evenly dispersed in the cyclopentane acid dispersion, which can achieve rapid contact between the nano-silica and the cyclopentane acid, which is conducive to the grafting reaction and ensures that the nano-silica can be fully grafted.
[0009] Preferably, the low temperature plasma treatment uses nitrogen and oxygen in a volume ratio of 1.5 to 9:1, a flow rate of 15 to 30 L / min, a voltage of 20 to 30 kV, and a frequency of 6 to 10 kHz for 1 to 5 minutes. Under the plasma treatment, the hydrogen supply agent and the oxygen supply agent react at the activation point to generate hydroxyl groups, which can ensure the surface treatment effect of nano silicon dioxide in the preferred case.
[0010] Preferably, the concentration of cyclohexane acid in the cyclohexane acid dispersion is 0.2-0.6 g / L.
[0011] Preferably, the preparation method of the cyclopentane acid dispersion is as follows: add polyacrylamide in an amount of 0.001-0.003 g / L to water, mix for 20-60 min at 40-60° C., heat to 70-80° C., add cyclopentane acid at a speed of 5000-7000 r / min, stir evenly, and obtain a cyclopentane acid dispersion.
[0012] Polyacrylamide as a thickener can increase the system viscosity of the cyclohexane acid dispersion, solve the problem of uneven dispersion of nano-silicon dioxide after plasma treatment, improve the dispersion uniformity of nano-silicon dioxide in cyclohexane acid, and ensure sufficient grafting of nano-silicon dioxide.
[0013] Further preferably, ethanol in an amount of 2 to 3 times the volume of the water is added.
[0014] For a smaller amount of cyclohexane acid dispersion, a small amount of polyacrylamide will lead to too high viscosity of the system. Therefore, adding the above amount of ethanol in combination with the above polyacrylamide concentration can ensure appropriate viscosity of the system and fluidity.
[0015] Preferably, the method for mixing the nano-silicon dioxide and the cyclohexane acid dispersion is as follows: adding the nano-silicon dioxide to the cyclohexane acid dispersion at a rotation speed of 5000-7000 r / min and a temperature of 70-80°C.
[0016] Preferably, the base asphalt has a softening point of above 46°C and a needle penetration of 60-70; the petroleum resin is a hydrogenated petroleum resin, with a softening point of 95-105°C and an acid value of less than 0.1 mgKOH / g. The excellent viscosity-increasing effect of hydrogenated petroleum resin can further increase the viscosity of the waterproofing roll asphalt and enhance the adhesion.
[0017] Preferably, the solubilizing agent is a mixture of naphthenic oil and catalytic cracking oil slurry in a mass ratio of 1:1, wherein the flash point of the naphthenic oil is greater than 220°C and the kinematic viscosity at 40°C is less than 50 mm 2 / s; the solid content of catalytic cracking oil slurry is less than 100μg / g and the sulfur content is less than 0.5%.
[0018] A method for preparing the modified waterproofing roll asphalt is characterized by comprising the following steps: 1) SBS polymer and solubilizer are mixed evenly and developed at 120-140℃ for 40-80min to obtain SBS solution; 2) The base asphalt is heated to 170-180°C, and the modified nano-silicon dioxide is added under stirring, and stirred for 30-50 minutes; the SBS solution obtained in step 1) is added, and stirred at 170-180°C and a stirring speed of 3000-4000 r / min for 60-80 minutes; 3) Add petroleum resin and continue stirring for 30 to 40 minutes to obtain modified waterproof membrane asphalt.
[0019] The matrix asphalt and the modified nano-silica particles are pre-mixed. Since the viscosity of the matrix asphalt drops significantly at high temperatures, the dispersion resistance of the modified nano-silica particles in the asphalt can be reduced, and the uniform dispersion of the nano-silica particles in the asphalt can be promoted. In addition, since the modified nano-silica particles have increased compatibility with the matrix asphalt, the surface-grafted cyclopentane acid and the molecular structure in the matrix asphalt are entangled with each other, and the size of the modified nano-silica particles does not change with temperature, which limits the shrinkage and expansion of the asphalt in the waterproof membrane under high and low temperature conditions, thereby increasing the durability of the waterproof membrane.
[0020] Using SBS as a modifier can improve the high and low temperature performance of waterproof coiled material asphalt. Since the addition of SBS will adsorb the light components in the matrix asphalt and cause a significant increase in viscosity, it is not conducive to the swelling and dispersion of SBS, resulting in poor modification effect. Therefore, SBS is mixed with a solubilizer in advance. Since the solubilizer is a low-viscosity oil, SBS can fully absorb the light components and swell, opening the molecular chains that are entangled with each other inside the SBS particles. When it is added to the matrix asphalt, it can avoid the viscosity of the modified system caused by the addition of SBS. Increase, limit the performance of SBS function. At the same time, the organic long chain on the surface of the nano-silicon dioxide particles is entangled with the SBS network structure, enhances the strength of the SBS network structure, improves the high temperature performance of the waterproof coiled material, and at the same time, the enhanced strength of the SBS network structure prevents the waterproof coiled material from breaking due to the poor compatibility of the nano-silicon dioxide particles with the matrix asphalt under low temperature and external force, and improves the low temperature performance of the waterproof coiled material. The above components work together to improve the high temperature performance and durability of the waterproof membrane, and solve the problem of poor compatibility between nano-silicon dioxide and asphalt, which causes the low temperature performance and adhesion of the modified waterproof membrane asphalt to decrease.
[0021] Compared with the prior art, the invention has the following beneficial effects: using low-temperature plasma to treat nano-silicon dioxide, the hydroxyl active groups on the surface of nano-silicon dioxide are increased, and the grafting activity on the surface of silicon dioxide is improved; cyclopentane acid is grafted on the surface of nano-silicon dioxide, and the grafting is sufficient to increase the compatibility of nano-silicon dioxide with matrix asphalt, improve the dispersion compatibility between inorganic nano-silicon dioxide and organic asphalt matrix, and improve the self-stability of modified waterproof coiled material asphalt; because cyclopentane acid has good compatibility with matrix asphalt, the modified nano-silicon dioxide particles with cyclopentane acid grafted on the surface can be quickly dissolved into the matrix asphalt, increase the adhesion of nano-silicon dioxide particles to matrix asphalt, prevent the nano-silicon dioxide particles from peeling off, and increase the durability and low-temperature performance of the waterproof coiled material; the modified nano-silicon dioxide particles with cyclopentane acid grafted on the surface have an acidic surface, which can increase the adhesion with alkaline building materials and increase the anti-peeling property of the waterproof coiled material. In addition, the anti-peeling property, low-temperature performance and durability of the modified waterproof coiled material asphalt are improved. DETAILED DESCRIPTION
[0022] The present invention is further described below with reference to the examples, and Example 1 is the best example of the present invention. In the following examples, the cyclohexane acid used is a commercially available product with an acid value of 200 mgKOH / g. The polyacrylamide used is a cationic polyacrylamide, a commercially available product with an ionicity of 50. The matrix asphalt is an imported crude oil with a density between 0.86 and 0.94 and a sulfur content of less than 0.5%, a softening point of ≥46°C, a needle penetration of 60 to 70, and a solubility of greater than 99.85%. The petroleum resin is a hydrogenated petroleum resin with a softening point of 95 to 105°C and an acid value of less than 0.1 mgKOH / g. The SBS polymer is the SBS produced by Sinopec Baling Branch, with an S / B weight ratio of 30 / 70 and a melt flow rate of 0.1 to 5 g•10 min -1 The solubilizer used is a mixture of naphthenic oil and catalytic cracking oil slurry in a mass ratio of 1:1, wherein the flash point of the naphthenic oil is greater than 220°C and the kinematic viscosity at 40°C is less than 50mm 2 / s; the solid content of catalytic cracking oil slurry is less than 100μg / g and the sulfur content is less than 0.5%.
[0023] Example 1 A modified waterproofing roll asphalt, the raw materials of which include 37kg of base asphalt, 5kg of petroleum resin, 15kg of SBS polymer, 24kg of solubilizer and 19kg of modified nano silicon dioxide.
[0024] Modified nano-silica is modified by the following steps: 1) After soaking for 75 minutes, the nano-silicon dioxide was filtered and placed in a plasma reactor, and treated for 5 minutes with nitrogen and oxygen in a volume ratio of 5:1, a flow rate of 20L / min, a voltage of 25kV, and a frequency of 7kHz.
[0025] 2) Anhydrous ethanol and deionized water were mixed in a weight ratio of 3:1, and polyacrylamide was added in an amount of 0.002 g / L. The mixture was mixed at 50°C and a rotation speed of 400 r / mim for 40 min. The mixture was heated to 75°C and a rotation speed of 6000 r / mim under shearing action, and cyclohexane acid was added to obtain a cyclohexane acid dispersion with a cyclohexane acid concentration of 0.4 g / L.
[0026] 3) While maintaining the rotation speed and temperature of step 2), the nano-silicon dioxide obtained in step 1) is slowly added to the excess cyclohexane acid dispersion and stirring is continued for 150 minutes.
[0027] 4) The solid was filtered, washed with ethanol, and dried in an oven at 80°C for 70 min to obtain modified nano-silica.
[0028] A method for preparing a modified waterproofing roll asphalt comprises the following steps: 1) SBS polymer and solubilizer are mixed evenly and placed in a 120-140°C oven for constant temperature development for 70 minutes to obtain SBS solution.
[0029] 2) The base asphalt was heated to 175°C, and the modified nano-silica was added under stirring at 900 rpm, and stirred for 40 min; the SBS solution obtained in step 1) was added, and stirred at 175°C and 3500 r / min for 70 min.
[0030] 3) Add petroleum resin and continue stirring for 35 minutes to obtain modified water-repellent membrane asphalt.
[0031] Example 2 A modified waterproofing roll asphalt is prepared based on Example 1, wherein the raw materials are 33 kg of base asphalt, 10 kg of petroleum resin, 19 kg of SBS polymer, 18 kg of solubilizer and 22 kg of modified nano-silicon dioxide, and other conditions are the same as those in Example 1.
[0032] Example 3 A modified waterproofing roll asphalt is prepared based on Example 1, wherein the raw materials are 45 kg of base asphalt, 7 kg of petroleum resin, 12 kg of SBS polymer, 21 kg of solubilizer and 15 kg of modified nano-silicon dioxide, and other conditions are the same as those in Example 1.
[0033] Example 4 A modified waterproofing roll asphalt is prepared based on Example 1, wherein the raw materials are 33 kg of base asphalt, 15 kg of petroleum resin, 15 kg of SBS polymer, 12 kg of solubilizer and 25 kg of modified nano-silicon dioxide, and other conditions are the same as those in Example 1.
[0034] Example 5 A modified waterproofing roll asphalt is prepared based on Example 1, wherein the raw materials are 41 kg of base asphalt, 7 kg of petroleum resin, 12 kg of SBS polymer, 17 kg of solubilizer and 22 kg of modified nano-silicon dioxide, and other conditions are the same as those in Example 1.
[0035] Example 6 A modified waterproofing roll asphalt is prepared based on Example 1, wherein the raw materials are 38 kg of base asphalt, 13 kg of petroleum resin, 22 kg of SBS polymer, 15 kg of solubilizer and 15 kg of modified nano-silicon dioxide, and other conditions are the same as those in Example 1.
[0036] Example 7 A modified waterproof roll asphalt, based on Example 1, in the cyclohexane acid dispersion of the nano-silicon dioxide modification step 2), the cyclohexane acid concentration is set to 0.2 g / L, and other conditions are the same as in Example 1.
[0037] Comparative Example 1 A modified waterproofing roll asphalt, based on Example 1, the nano-silicon dioxide modification step 1) is set as follows: A 2% by mass dilute hydrochloric acid solution was used and heated to 60° C., and then nano-silicon dioxide powder was added under stirring, and the acid-treated nano-silicon dioxide powder was obtained after filtration. Other conditions were the same as those in Example 1.
[0038] Comparative Example 2 A modified waterproof roll asphalt, based on Example 1, wherein the cyclohexane acid in the nano-silicon dioxide modification step 2) is replaced by stearic acid, and other conditions are the same as those in Example 1.
[0039] Comparative Example 3 A modified waterproof roll asphalt, based on Example 1, when adding nano silicon dioxide in the nano silicon dioxide modification step 3), the system temperature is set to 60°C, the continuous stirring time is set to 200 minutes, and other conditions are the same as Example 1.
[0040] Comparative Example 4 A modified waterproofing roll asphalt is provided. Based on Example 1, the nano silicon dioxide is not modified, and other conditions are the same as those of Example 1.
[0041] Comparative Example 5 A modified waterproof roll asphalt, based on Example 1, the nano-silicon dioxide modification is only processed by step 1) without taking other modification steps, and other conditions are the same as Example 1.
[0042] Comparative Example 6 A modified waterproof roll asphalt, based on Example 1, is modified with nano silicon dioxide 2) without preparing a cyclopentane acid dispersion, step 3) the nano silicon dioxide is directly stirred with cyclopentane acid at 75° C. and a shear rate of 6000 r / min for 150 min, and other conditions are the same as in Example 1.
[0043] Comparative Example 7 A modified waterproof roll asphalt is provided. Based on Example 1, the nano-silicon dioxide modification is performed without the step 1) of low-temperature plasma treatment, and the following steps are directly performed. Other conditions are the same as those in Example 1.
[0044] Comparative Example 8 A modified waterproof roll asphalt, based on Example 1, the nano-silicon dioxide modification is not treated by the cyclohexane acid dispersion obtained in step 2), but in step 3), a silane coupling agent is used to stir for 150 minutes at 70° C. and a rotation speed and shear rate of 6000 r / min, and other conditions are the same as in Example 1.
[0045] Comparative Example 9 A modified waterproof roll asphalt, based on Example 1, nano-silicon dioxide modification uses only oleic acid with a concentration of 2%, and is modified by stirring at 75° C. and a rotation speed of 6000 r / min for 150 minutes, and other conditions are the same as in Example 1.
[0046] Comparative Example 10 A method for preparing a modified waterproofing roll asphalt is provided. On the basis of Example 1, a solubilizer is added to a base asphalt at 175° C. and a stirring speed of 900 rpm, the rotation speed is set to 3500 rpm, nano-silicon dioxide, SBS polymer, and petroleum resin are modified in sequence, and stirred for 70 minutes at 175° C. and a stirring speed of 3500 r / min. The base asphalt and the modified nano-silicon dioxide, the solubilizer, and the SBS polymer are not pre-mixed, and other conditions are the same as in Example 1.
[0047] Comparative Example 11 A modified waterproof roll asphalt, based on Example 1, the modified nano silicon dioxide is replaced by talcum powder, and other conditions are the same as those of Example 1.
[0048] Performance Testing The modified waterproofing roll asphalt obtained in the above examples and comparative examples was made into waterproofing rolls, which were composed of an upper protective film, an upper modified waterproofing roll asphalt, a base layer, a lower modified waterproofing roll asphalt, and a lower protective film from top to bottom. The protective film was a PET isolation film; the base layer was a polyurethane base layer, and the thickness of the base layer was 5 mm; the thickness of the binder was 3 mm.
[0049] The modified asphalt waterproofing membrane is evenly covered on the upper and lower parts of the base layer, and then covered with the upper protective film and the lower protective film and cooled.
[0050] Low temperature flexibility is tested according to JG / T207-2014.
[0051] The peel strength is tested according to GB / T23457-2009.
[0052] Aggregate adhesion was tested according to JTG F40-2004.
[0053] The test results are shown in Table 1 below.
[0054] Table 1 Performance test results .
[0055] By comparing the test results of the embodiment and the comparative example, it can be seen that the nano-silicon dioxide modified waterproofing coiled material prepared by the present invention has excellent low-temperature flexibility, good adhesion and durability. By modifying the inorganic nano-silicon dioxide in steps, the problem of poor compatibility between nano-silicon dioxide particles and matrix asphalt is solved, the adverse effect of poor low-temperature flexibility of waterproofing coiled material asphalt due to the addition of nano-silicon dioxide materials is improved, the peel strength of the waterproofing coiled material is increased, and the anti-stripping property of the waterproofing coiled material is improved. At the same time, according to the evaluation results of the water boiling method, it can be found that by improving the compatibility of nano-materials and waterproofing coiled material asphalt, the adhesion between the waterproofing coiled material and the aggregate is increased, the adhesion between the waterproofing coiled material and the building materials is strengthened, and the durability of the waterproofing coiled material is improved.
[0056] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A modified waterproofing roll asphalt, characterized in that: The raw materials include 30-45 parts of base asphalt, 5-15 parts of petroleum resin, 12-22 parts of SBS polymer, 12-24 parts of solubilizer, and 15-25 parts of modified nano-silicon dioxide by weight; Wherein, the modified nano silicon dioxide is modified by the following steps: 1) Low temperature plasma surface treatment of nano-silicon dioxide; 2) After the nano-silica and cyclohexane acid dispersion are mixed and stirred evenly, react at 70-80°C for 100-200 minutes; 3) Separating, washing and drying the products to obtain modified nano-silica.
2. The modified waterproofing roll asphalt according to claim 1, characterized in that: The low-temperature plasma treatment uses nitrogen and oxygen in a volume ratio of 1.5-9:1, a flow rate of 15-30 L / min, a voltage of 20-30 kV, and a frequency of 6-10 kHz for 1-5 minutes.
3. The modified waterproofing roll asphalt according to claim 1, characterized in that: The concentration of cyclohexane acid in the cyclohexane acid dispersion is 0.2-0.6 g / L.
4. The modified waterproofing roll asphalt according to claim 1, characterized in that: The preparation method of the cyclohexane acid dispersion is as follows: add polyacrylamide in an amount of 0.001-0.003 g / L into water, mix for 20-60 min at 40-60° C., heat to 70-80° C., add cyclohexane acid at a speed of 5000-7000 r / min, stir evenly, and obtain the cyclohexane acid dispersion.
5. The modified waterproofing roll asphalt according to claim 4, characterized in that: The water is also added with ethanol in an amount of 2 to 3 times its volume.
6. The modified waterproofing roll asphalt according to claim 1, characterized in that: The mixing method of the nano silicon dioxide and the cyclohexane acid dispersion is as follows: the cyclohexane acid dispersion is mixed with the nano silicon dioxide at a speed of 5000-7000 r / min and a temperature of 70-80°C.
7. The modified waterproofing roll asphalt according to claim 1, characterized in that: The base asphalt has a softening point of above 46°C and a needle penetration of 60-70; the petroleum resin is a hydrogenated petroleum resin with a softening point of 95-105°C and an acid value of less than 0.1 mgKOH / g.
8. The modified waterproofing roll asphalt according to claim 1, characterized in that: The solubilizer is a mixture of naphthenic oil and catalytic cracking oil slurry in a mass ratio of 1:1, wherein the flash point of the naphthenic oil is greater than 220°C and the kinematic viscosity at 40°C is less than 50mm 2 / s; the solid content of catalytic cracking oil slurry is less than 100μg / g and the sulfur content is less than 0.5%.
9. A method for preparing the modified asphalt waterproofing membrane according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) SBS polymer and solubilizer are mixed evenly and developed at 120-140℃ for 40-80min to obtain SBS solution; 2) The base asphalt is heated to 170-180°C, and the modified nano-silicon dioxide is added under stirring, and stirred for 30-50 minutes; the SBS solution obtained in step 1) is added, and stirred at 170-180°C and a stirring speed of 3000-4000 r / min for 60-80 minutes; 3) Add petroleum resin and continue stirring for 30 to 40 minutes to obtain modified waterproof membrane asphalt.
Citation Information
Patent Citations
Surface modification method of nanosilicon dioxide
CN103013182A
A polymer-modified bitumen waterproof membrane and its preparation method
CN108274844B
Polymer modified asphalt waterproof roll and preparation method thereof
CN108274844A
Low-temperature-resistant self-adhesive polymer modified asphalt waterproof coiled material and preparation method thereof
CN116463072A